Combination of high hoop stress tolerance and a small screening current-induced field for an advanced Bi-2223 conductor coil at 4.2 K in an external field. (23rd October 2015) - Yanagisawa, Y; Xu, Y; Iguchi, S; Hamada, M; Matsumoto, S; Nishijima, G; Nakagome, H; Takao, T; Suematsu, H; Oshima, Y; Jin, X; Takahashi, M; et al.
Abstract: An advanced Bi-2223 conductor with Ni–Cr reinforcement is a likely candidate to achieve a compact super-high field nuclear magnetic resonance (NMR) magnet capable of operation beyond 1 GHz (23.5 T). However, the conductors must show both high hoop stress tolerance, typically >300 MPa, and a small screening current-induced magnetic field, both of which are essential for a compact magnet generating a highly accurate field. These two conditions have not yet been demonstrated in a working coil. This is the first paper to systematically investigate both characteristics for a layer-wound coil made with the advanced Bi-2223 conductor operated mainly at 4.2 K in an external field of ≤17 T. The coil tolerated a hoop stress of 370 MPa, even though the conductor had a bending strain corresponding to a diameter of 120 mm. On the other hand, the coil showed a notable screening current-induced field in a low external field, which may be explained by weak-link and direct contacts between highly packed Bi-2223 filaments in the silver matrix. The field sharply decreased with increasing external field between 0–1 T. Thus, the conductor should be useful for inner coils in compact super-high field NMR magnets.